2002
DOI: 10.1080/10407780252780199
|View full text |Cite
|
Sign up to set email alerts
|

Natural Convection in Cubical Enclosures With Thermal Sources on Adjacent Vertical Walls

Abstract: Natural convection in a cubical enclosure with a hot source centered on a vertical wall and with an adjacent, fully cooled vertical wall was numerically investigated for Rayleigh numbers (Ras) of 10 3 -4 £ 10 6 . At Ra < 10 5 the heat transfer strongly depends on the hot sector side and its dependence on Ra is weak. Opposite characteristics occur at very high Ra, and there is a long transition between these two regimes. This behavior is caused by a mixing pattern, which, at low Ra, is similar to the one found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…They investigated the effect of aspect ratio and inclination of the cavity on the heat transfer process. Other relevant papers which also deal with localized heated surfaces may be found in references [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…They investigated the effect of aspect ratio and inclination of the cavity on the heat transfer process. Other relevant papers which also deal with localized heated surfaces may be found in references [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Ju and Chen [14] have investigated natural convection in an enclosure with a discrete heater at the one of its vertical walls. Natural convection in an enclosure with thermal sources on its adjacent walls has been examined by Fredrick and Berbakow [15]. The partially cooled and heated enclosures have been the subject of the research by Turkoglu and Yucel [16].…”
Section: Introductionmentioning
confidence: 99%
“…His results indicated that Nusselt numbers became more than that computed for a side heated cavity at low values of Rayleigh number. Frederick and Berbakow [12] numerically studied the natural convection in a cubical enclosure with a hot source centered on a vertical wall and with an adjacent, fully cooled vertical wall. They concluded that the heat transfer had a weak dependent on the Rayleigh number.…”
Section: Introductionmentioning
confidence: 99%